Failure to launch? The influence of limb autotomy on the escape behavior of a semiaquatic grasshopper Paroxya atlantica (Acrididae) - Bateman, Bill; Fleming, P. (Oxford University Press, 2011)
Autotomy is an extreme escape tactic where an animal sheds an appendage to escape predation. Many species alter their behaviour postautotomy to compensate for this loss. We examined the escape behavior in the field of a semiaquatic grasshopper (Paroxyaatlantica) that could escape either by flight and landing in vegetation or flight and landing in water and swimming to safety. Wepredicted that animals missing a hind limb would be more reactive (i.e., have longer flight initiation distances; FID) and would prefer to escape to vegetation rather than to water as loss of a limb is likely to reduce swimming ability. However, our predictions were not supported. FID in autotomized animals was not different from that in intact animals. Furthermore, although autotomized grasshoppers paused more often and swam slower than intact individuals, autotomized rasshoppers more often escaped to water, reaching it via shorter flights that were lateral to the approach of the observer (intact grasshoppers more often flew directly away from the observer). We also noted differences in behavior before disturbance: Autotomised animals perched lower onemergent vegetation than did intact ones, presumably in readiness for escape via water, and also showed a greater likelihood to hide (squirreling) from the approaching observer prior to launch into flight. It seems likely that the reduced flight distance andgreater propensity to land in water for autotomized P. atlantica may reflect a failure to launch from their perch due to loss ofa jumping back leg. Key words: distance fled, escape tactics, escape trajectory, flight initiation distance, Orthoptera, predationrisk.